1985
DOI: 10.1029/jb090ib12p09986
|View full text |Cite
|
Sign up to set email alerts
|

Transform deformation of tertiary rocks along the Tjornes Fracture Zone, north central Iceland

Abstract: Significant fracture zone deformation has been imparted to Tertiary lavas on the peninsula (Flateyjarskagi) located between Eyjafjördur and Skjálfandi in north central Iceland. The region lies immediately south of the Flatey fault, one of a series of WNW trending, left‐stepping faults comprising the right‐lateral, oblique slip Húsavík‐Flatey fault system (HFFS). The HFFS defines the present southern margin of the 70 to 80‐km‐wide Tjörnes Fracture Zone (TFZ). Lava bedding, dikes, and faults in the western half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(131 citation statements)
references
References 70 publications
4
125
2
Order By: Relevance
“…Regarding the slip amount along each of these three faults, the HFF, which is generally regarded as the main plate boundary structure of the TFZ, is marked onland as a geomorphological feature over a distance of 25 km across the Tjörnes peninsula and by a 3–5 km wide zone of intense deformation [e.g., Fjäder et al , 1994; Garcia and Dhont , 2005]. The minimum cumulative right‐lateral slip along the HFF is 5–10 km or 20 km and may be as large as 60 km [ Saemundsson , 1974; Young et al , 1985] whereas its vertical displacement is larger than 200 m and may reach 1400 m [ Gudmundsson et al , 1993]. The DF is thought to have absorbed little displacement because of its discrete onland expression.…”
Section: Tjörnes Fracture Zonementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the slip amount along each of these three faults, the HFF, which is generally regarded as the main plate boundary structure of the TFZ, is marked onland as a geomorphological feature over a distance of 25 km across the Tjörnes peninsula and by a 3–5 km wide zone of intense deformation [e.g., Fjäder et al , 1994; Garcia and Dhont , 2005]. The minimum cumulative right‐lateral slip along the HFF is 5–10 km or 20 km and may be as large as 60 km [ Saemundsson , 1974; Young et al , 1985] whereas its vertical displacement is larger than 200 m and may reach 1400 m [ Gudmundsson et al , 1993]. The DF is thought to have absorbed little displacement because of its discrete onland expression.…”
Section: Tjörnes Fracture Zonementioning
confidence: 99%
“…(a and b) Maximal horizontal stress S Hmax inferred from inversion of fault‐slip data. Trends of dikes and trace of normal faults in the Flateyjarskagi peninsula [ Young et al , 1985] are also shown. (c) (S Hmax ) from focal earthquakes inversion.…”
Section: Stress Distribution In the Tjörnes Fracture Zonementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Tryggvason (1973) suggested that such fault can reach an overall vertical offset of as much as 1400 m, although the location of this onshore measurement remains undefined. Saemundsson (1974), based on local geology, proposed a cumulated total component of rightlateral displacement ranging from 5 to 10 km near the town of Husavik whereas, according to Young et al (1985) it may amount to 20 km.…”
Section: Geologic-tectonic Frameworkmentioning
confidence: 99%
“…The HFF has its main on-land exposure on the north coast of the Flateyjarskagi Peninsula (Young et al, 1985;Gudmundsson, 1993;Fjäder et al, 1994;Garcia et al, 2002;Garcia and Dhonit, 2005). There the fault is marked by Fig.…”
Section: Flateyjarskagimentioning
confidence: 94%